2019
DOI: 10.1101/865360
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multivariable G-E interplay in the prediction of educational achievement

Abstract: Polygenic scores are increasingly powerful predictors of educational achievement. It is unclear, however, how sets of polygenic scores, which partly capture environmental effects, perform jointly with sets of environmental measures, which are themselves heritable, in prediction models of educational achievement.Here, for the first time, we systematically investigate gene-environment correlation (rGE) and interaction (GxE) in the joint analysis of multiple genome-wide polygenic scores (GPS) and multiple environ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 71 publications
1
39
2
Order By: Relevance
“…For example, if twin data are available, direction of causation models (if there are different modes of inheritance for the traits under study) [44] and genetic cross-lagged models [45] provide genetically sensitive methods for studying causality. In the absence of family data, one can still try to separate genetic from environmental effects if DNA data are available, for example by incorporating the effect of polygenic scores (scores that reflect individuals' genetic predisposition for a trait based on results from genome-wide association studies) in mediation models [46] or Mendelian randomization models [47]. From a research perspective, it is important that investigations into adolescent mental health correlates take into consideration that these associations might reflect a shared genetic liability.…”
Section: Discussionmentioning
confidence: 99%
“…For example, if twin data are available, direction of causation models (if there are different modes of inheritance for the traits under study) [44] and genetic cross-lagged models [45] provide genetically sensitive methods for studying causality. In the absence of family data, one can still try to separate genetic from environmental effects if DNA data are available, for example by incorporating the effect of polygenic scores (scores that reflect individuals' genetic predisposition for a trait based on results from genome-wide association studies) in mediation models [46] or Mendelian randomization models [47]. From a research perspective, it is important that investigations into adolescent mental health correlates take into consideration that these associations might reflect a shared genetic liability.…”
Section: Discussionmentioning
confidence: 99%
“…Although an extensive, conclusive body of empirical evidence has shown that correlations between genetic factors and environments are commonplace, G×Es remain to be reliably demonstrated (Duncan & Keller, 2011; Manuck & McCaffery, 2014; Tucker-Drob & Bates, 2016). For example, a recent large-scale study that tested GrEs and G×Es across multiple genotypes, phenotypes, and environments in the prediction of educational achievement observed systematic GrEs but concluded that the contributions of G×Es were random, weak, and negligible (Allegrini et al, 2020). Compared with detecting direct effects of genotypes on phenotypes (i.e., GrE), identifying G×Es is statistically more demanding because to be adequately powered, interaction models require much larger sample sizes than tests of direct effects (Duncan & Keller, 2011; Moffitt et al, 2006).…”
Section: Genes In Their Environmentsmentioning
confidence: 99%
“…One notable example is educational achievement. While early GWAS-based models explained only around 2% of the variance (Rietveld et al, 2013), current models explain as much as 20% (Allegrini et al, 2019;Lee et al, 2018;Selzam et al, 2018;von Stumm et al, 2020). Similar improvements in levels of predictive performance can be observed for other complex phenotypes, such as personality (Power & Pluess, 2015;Vinkhuyzen et al, 2012) and psychiatric traits (Schizophrenia Working Group of the Psychiatric Genomics Consortium, 2014; Visscher et al, 2012;Wray et al, 2014).…”
Section: Qualitative Benchmarks In Working Memory Researchmentioning
confidence: 80%